Mode-specific quantum dynamics and kinetics of the hydrogen abstraction reaction OH + H2O → H2O + OH. Issue 43 (24th October 2019) - Zheng, Rui; Zhu, Yongfa; Song, Hongwei
Abstract : The synergistic effect between the reactant stretching and bending modes on promoting the reaction. Abstract : Hydrogen abstraction processes are prevalent in a wide range of chemically active environments. In this work, the prototypical hydrogen exchange reaction OH + H2 O → H2 O + OH is investigated on an accurate ab initio based potential energy surface using an initial state-selected time-dependent wave packet method. Exciting either the symmetric stretching mode or the antisymmetric stretching mode of the reactant H2 O promotes the reaction more than exciting the bending mode. The vibrational energy initially deposited in H2 O is more efficient than the translational energy in promoting the reaction. There exists a remarkable synergistic effect between the stretching mode and the bending mode as the efficacy for the combination band excitation is larger than the sum of individual excitations. The mode-specific dynamics is partially rationalized by the sudden vector projection model. Besides, the mode-specific rate constants apparently exhibit a strong non-Arrhenius behavior at low and moderate temperatures.